Vaccination against Lyme disease: past, present, and future - Embers, Monica E.; Narasimhan, Sukanya (Frontiers in Cellular and Infection Microbiology, 2013)
Lyme borreliosis is a zoonotic disease caused by Borrelia burgdorferi sensu lato bacteria transmitted to humans and domestic animals by the bite of an Ixodes spp. tick (deer tick). Despite improvements in diagnostic tests and public awareness of Lyme disease, the reported cases have increased over the past decade to approximately 30,000 per year. Limitations and failed public acceptance of a human vaccine, comprised of the outer surface A (OspA) lipoprotein of B. burgdorferi, led to its demise, yet current research has opened doors to new strategies for protection against Lyme disease. In this review we discuss the enzootic cycle of B. burgdorferi, and the unique opportunities it poses to block infection or transmission at different levels. We present the correlates of protection for this infectious disease, the pros and cons of past vaccination strategies, and new paradigms for future vaccine design that would include elements of both the vector and the pathogen.